2003
DOI: 10.1097/01.shk.0000048904.46342.22
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and Hepatosplanchnic Hemodynamic and Metabolic Effects of the PARP Inhibitor PJ34 During Hyperdynamic Porcine Endotoxemia

Abstract: Activation of the poly(ADP-ribose)polymerase (PARP), a highly energy-consuming DNA-repairing enzyme, plays a crucial role in the pathogenesis of multiorgan failure. Most results, however, were derived from experiments with hypodynamic shock states characterized by a markedly decreased cardiac output (CO) and/or using a pretreatment approach. Therefore, we investigated the effects of the novel potent and selective PARP-1 inhibitor PJ34 in a posttreatment model of long-term, volume-resuscitated porcine endotoxem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Importantly, the effects of PJ34 were associated with a suppression of myocardial poly(ADP-ribose) immunoreactivity, supporting the notion of a PARP-1-dependent cardiodepressive mechanism in this clinically relevant model of septic shock [77]. Furthermore, in another model of volume-resuscitated porcine endotoxemia, PJ34 also improved cardiac output and increased stroke volume, which was most likely attributable to a direct positive inotropic effect [86].…”
Section: Parp-1 Activation Is Associated With Myocardial Depressionmentioning
confidence: 84%
“…Importantly, the effects of PJ34 were associated with a suppression of myocardial poly(ADP-ribose) immunoreactivity, supporting the notion of a PARP-1-dependent cardiodepressive mechanism in this clinically relevant model of septic shock [77]. Furthermore, in another model of volume-resuscitated porcine endotoxemia, PJ34 also improved cardiac output and increased stroke volume, which was most likely attributable to a direct positive inotropic effect [86].…”
Section: Parp-1 Activation Is Associated With Myocardial Depressionmentioning
confidence: 84%
“…The most significant amelioration was seen on MAP, RBF and renal oxygen metabolism. It is reported that suppression of PARP could influence both vascular and hemodynamic function [15,25] by upregulating the CO, attenuating cardiomyocyte dysfunction and reducing the SVR [26,27,28]. Hans et al [29] presented that PARP-1 gene deletions prominently prevent the faltering of hemodynamic parameters in cardiac hypertrophy by directly effecting MMP-9 and TIMP-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, 3-aminobenzamide is considered to be a poor inhibitor of PARP and has pronounced toxicity in vivo. On the other hand, novel, potent PARP-1 inhibitors were found to protect against LPS-induced tissue damage Ivanyi et al, 2003;Veres et al, 2003). Disruption of the PARP gene suppresses LPS-induced cytokine expression and NF-B activation (Oliver et al, 1999).…”
mentioning
confidence: 99%